Qualitative Analysis of Factors Affecting Taxpayer Compliance in Paying Income Tax Article 21 on PTPN IV Regional 1 Kebun Rantau Prapat Employees - Hamdani, Hamdani; Batubara, Chuzaimah (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This study aims to identify factors that influence employee compliance of PTPN IV Regional 1 Kebun Rantau Prapat in paying Income Tax (PPh) Article 21. The method used is descriptive qualitative research through observation and document study. The results of the study indicate that tax non-compliance is mainly caused by the lack of public understanding of their status as taxpayers and the obligation to pay taxes. Other factors that influence tax compliance include tax awareness and knowledge, socialization, sanctions, incentives, and tax audits. Increasing tax awareness can increase compliance, while lack of socialization and understanding of tax regulations has a negative impact. In addition, the implementation of appropriate tax incentives and strict supervision through sanctions and tax audits can also increase taxpayer compliance. Therefore, more intensive socialization and education efforts are needed as well as more effective tax policies to improve employee tax compliance. This study is expected to be a reference for policy makers in designing better strategies to increase state tax revenues.